Description of the flow in a linear cascade with an upstream cavity Part 1: Influence of turbulence (draft). (15th March 2020) - Fiore, M.; Gourdain, N.; Boussuge, J.-F.; lippinois, E.
Highlights: LES with inlet turbulence injection provides the best matching with experiments. The free-stream turbulence cancels the suction side boundary layer separation. The migration of secondary vortices is modified by hub/shroud boundary layer state. The free-stream turbulence cancels the Kelvin–Helmholtz instability at the seal. Abstract: In gas turbines, transitional flows are likely to occur over many components depending on the geometrical arrangement, inlet turbulence and Reynolds number. In the case of a low-pressure turbine, the transition from a laminar to a turbulent boundary layer is generally either a bypass process due to free stream turbulence or a separation-induced transition due to the adverse pressure gradient on the blade. The overall blade losses and the operating point are strongly dependent on the ability to predict this boundary layer state, the size and length of the separation bubble. Therefore, turbomachinery designers require tools which accurately predict the laminar-turbulent transition. The Reynolds Averaged Navier–Stokes (RANS) formalism is currently commonly used due a to relatively low computational cost. Except particular developments, this approach is not suited to predict transition processes. The Large Eddy-Simulation (LES) approach is able to predict transition processes at a higher computational cost making it suitable for low-pressure turbine applications in conjunction with inlet turbulence injection since the free-stream turbulence is generally non-negligible and affect near-wall flow behavior. The present study introduces a description of the flow in a linear cascade with an upstream hub cavity at a Reynolds number representative of low-pressure turbines by three different approaches (RANS, LES and LES with inlet turbulence injection). This study shows the influence of turbulence modelling and turbulence injection at the inlet of the domain on the boundary layer state at hub and shroud modifying the secondary vortices radial migration in the blade passage and the cancelling of suction side separation bubble at high free-stream turbulence. The Kevin–Helmholtz instability at the rim seal interface is also cancelled at high free-stream turbulence.